High-resolution MR imaging of the arterial wall in moyamoya disease. (1st January 2015) - Yuan, Min; Liu, Zhi-qiang; Wang, Zhi-qiang; Li, Bin; Xu, Li-jun; Xiao, Xin-lan
Highlights: Different types of middle cerebral artery stenosis are identified by HRMRI. The differences between MMD and intracranial atherosclerotic stenosis are elucidated by HRMRI. Outer diameter and wall thickness of the MCAs in different MRA stages are compared. The possible mechanism of arterial progressive stenosis in MMD is analyzed. Abstract: High resolution magnetic resonance imaging (HRMRI) has been developed as an emerging tool for evaluating intracranial arterial disease. We aimed to analyze the progression of diseased arterial walls in moyamoya disease (MMD) and further elucidate differences compared to intracranial atherosclerotic stenosis using HRMRI. The population of this HRMRI study consisted of 21 patients with MMD and 44 patients with atherosclerotic middle cerebral artery (MCA) stenosis. The cross-sectional images of the MCA wall on HRMRI were compared between the two groups based on outer diameter, wall thickness, luminal stenotic morphology, signal intensity, collateral vascular structures adjacent to stenotic position. In addition, stage classification based on MRA finding was used to depict the course of moyamoya disease. We compared outer diameter and wall thickness of the MCAs in different MRA stages. As a result, the outer diameter and wall thickness of MCAs were significantly smaller in the MMD group than in the atherosclerosis group (outer diameter: MMD 2.01 ± 0.31 mm vs. atherosclerosis 3.31 ± 0.37 mm, p  < 0.001 and wall thickness: MMD 0.39 ± 0.19 mm vs. atherosclerosis 1.64 ± 0.38 mm, p  < 0.001). The concentric stenosis (91.4% in MMD vs. 36.9% in atherosclerosis group, p  < 0.001), homogeneous signal intensity (85.7% in MMD vs. 32.6% in atherosclerosis group, p  < 0.001) and collateral vascular structures (54.3% in MMD vs. 8.7% in atherosclerosis group, p  < 0.001) were more common in MMD patients. In addition, the outer diameter of MCAs in MMD was significantly different between MRA stage 1 and MRA stage 3 or 4 (MRA stage 1 vs. MRA stage 3, Nemenyi test p  = 0.005 and MRA stage 1 vs. MRA stage 4, Nemenyi test p  = 0.009). But the wall thickness of MCAs was no significantly different in different MRA stages (Kruskal–wallis H test, p  = 0.074). We conclude that HRMRI may be used to identify different types of middle cerebral artery stenosis. MMD was characterized by concentric stenosis, homogeneous signal intensity, and collateral vascular structures in the affected MCA segments by HRMRI. Pathological shrinkage of MCA was an important phenomenon in MMD progression.